Do internships educate students for employability? : a case study of employer experiences of the TSiBA internship model - Josias, Morea (School of Education, 2015)
This study investigates employer’s views about whether internships educate students for employability. A case study of a local tertiary institution, the Tertiary School in Business Administration (TSiBA), was undertaken to determine whether the TSiBA internship model equipped final year students with employable skills.